Optimizing Transitions of Care: The Impact of Pharmacist-Led Discharge Interventions on Readmissions and Healthcare Costs - Omar El Khatib; Wasim S. El Nekidy; Emna N. A. Abidi; Fatima AlSalama; Noor Isam; Regina Aspe Velasco; Sara AlJabi; Joanna Saleh (Hospital Pharmacy, 2026)
Purpose: Medication discrepancies at hospital discharge contribute to readmissions and adverse outcomes. Although national groups endorse pharmacist-led discharge medication reconciliation, implementation varies. We examined the effect of pharmacist-led discharge medication reconciliation on 30-day hospital readmission odds and financial outcomes after launching a transitions-of-care discharge service at our quaternary medical center. Methods: This retrospective observational study evaluated discharged in-patients who received pharmacist-led discharge medication reconciliation (study intervention) versus those who did not. Discharges from intensive care, oncology, and transplant services were excluded. Patient-encounter data and pharmacist study intervention were analyzed, with 30-day hospital readmission odds as the primary endpoint. Pharmacist documented clinical interventions conducted during the study intervention were also analyzed for secondary outcomes of patient and cost saving outcomes. Generalized estimating equations accounted for repeated encounters and assessed the influence of discharge medication reconciliation on 30-day hospital readmission odds, including interaction with case mix index. Results: Of 14 592 discharges, 12 367 (84.8%) met the inclusion criteria, and 8469 (68.0%) received pharmacist-led discharge medication reconciliation, which is the study intervention. In the fourth quarter, 3170 discharges were evaluated. Among patients who did not receive pharmacist-led discharge medication reconciliation (n = 871), a not receiving PL-DMR was associated with significantly greater 30-day hospital readmission odds (OR, 1.06; 95% CI 1.00-1.11; P = .036). Patients discharged from the Digestive Diseases Institute without pharmacist-led discharge medication reconciliation had higher odds of readmission (OR, 2.14; 95% CI 1.14-3.99; P = .017), although this association was not significant after accounting for interaction with case mix index in the intervention model (OR, 1.47; 95% CI 0.52-4.19; P = .467). Surgical patients who did not receive pharmacist-led discharge medication reconciliation also showed a non-significant increase in 30-day hospital readmission odds (OR, 2.73; 95% CI 0.90-8.29; P = 0.076). In 2024, 437 pharmacist documented clinical interventions during the process of discharge medication reconciliation contributed an estimated $240 448.77 in cost avoidance. Conclusion: Pharmacist-led discharge medication reconciliation mitigated complexity-related readmissions, resulting in cost savings. These findings support implementation of transitions-of-care services.